2018
DOI: 10.3390/ijms19041264
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pharmacology of VEGF-A Isoforms: Binding and Signalling at VEGFR2

Abstract: Vascular endothelial growth factor-A (VEGF-A) is a key mediator of angiogenesis, signalling via the class IV tyrosine kinase receptor family of VEGF Receptors (VEGFRs). Although VEGF-A ligands bind to both VEGFR1 and VEGFR2, they primarily signal via VEGFR2 leading to endothelial cell proliferation, survival, migration and vascular permeability. Distinct VEGF-A isoforms result from alternative splicing of the Vegfa gene at exon 8, resulting in VEGFxxxa or VEGFxxxb isoforms. Alternative splicing events at exons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
312
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(336 citation statements)
references
References 231 publications
13
312
0
11
Order By: Relevance
“…Angiogenesis, the growth of new blood vessels from existing vascular networks, is an important physiological process that can be dysregulated in numerous pathologies including cancer and age‐related macular degeneration (Chung & Ferrara, ; Peach, Mignone, et al, ). VEGF‐A is a key mediator of both angiogenesis and vascular permeability, primarily signalling via its cognate receptor VEGF receptor 2 (VEGFR2; Alexander et al, ; Simons, Gordon, & Claesson‐Welsh, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiogenesis, the growth of new blood vessels from existing vascular networks, is an important physiological process that can be dysregulated in numerous pathologies including cancer and age‐related macular degeneration (Chung & Ferrara, ; Peach, Mignone, et al, ). VEGF‐A is a key mediator of both angiogenesis and vascular permeability, primarily signalling via its cognate receptor VEGF receptor 2 (VEGFR2; Alexander et al, ; Simons, Gordon, & Claesson‐Welsh, ).…”
Section: Introductionmentioning
confidence: 99%
“…The residues present within each VEGF‐A isoform determine whether they can interact with other membrane proteins (e.g., neuropilin 1; Cébe Suarez et al, ; Parker, Xu, Li, & Vander Kooi, ; Guo & Vander Kooi, ; Peach, Kilpatrick, et al, ) and extracellular matrix components (Krilleke et al, ; Vempati, Popel, & Mac Gabhann, ). This causes isoforms to vary in their bioavailability and signalling outcomes with many isoforms acting as partial agonists relative to VEGF 165 a (Peach, Mignone, et al, ). VEGF‐A isoforms also have distinct expression profiles in health and disease, such as down‐regulation of VEGF 165 b in numerous cancer types (Bates et al, ; Pritchard‐Jones et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This setting allowed us to determine the unique effects of ECM binding Vegfa isoforms on EC behaviors during embryogenesis. Previous studies in developing mice (Ruhrberg et al, 2002; Stalmans et al, 2002), disease settings (Brash et al, 2019; Cheng et al, 1997; Guo et al, 2001; Kazemi et al, 2016) and in cultured ECs (Chen et al, 2010; Delcombel et al, 2013; Fearnley et al, 2016; Herve et al, 2005; Park et al, 1993; Shiying et al, 2017) carefully investigated the effects of the different VEGF isoforms on cellular behaviors (for review see (Peach et al, 2018; Woolard et al, 2009)). Some studies suggested that there are no differences in the ability of various VEGFA isoforms to support EC proliferation (Ruhrberg et al, 2002), while others showed that ECs cultured on ECM derived from cells expressing VEGF189 or VEGF206 proliferated more strongly than those cultured in the presence of VEGF165 (Park et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Several VEGF family members, including VEGF‐A, VEGF‐B, VEGF‐C, VEGF‐D, and PlGF, are known to participate in the regulation of angiogenesis. Vascular endothelial growth factors act by binding with high affinity to receptor tyrosine kinases, VEGFR1‐R3; among these VEGF binding events, VEGF‐A binding to VEGFR2 comprises the main activating signal for angiogenesis . Importantly, VEGF‐A signaling through VEGFR2 is also the key driver for the neovascular growth known to support solid tumor progression .…”
Section: Introductionmentioning
confidence: 99%